STUDYING OF FUNCTIONAL CONDITION OF THE SMALL INTESTINE IN CHOLELITHIASIS - Ya. M. Vakhrushev; A. P. Lukashevich; A. Yu. Gorbunov (SINAPS LLC, 2015)
Aim. Complex research of the functional condition of the small intestine in different stages of cholelithiasis.Materials and methods. 47 patients with different stages of cholelithiasis were examined. There were 29 patients with the first (prestone) stage and 18 - with the second (stone) stage of cholelithiasis. In an assessment of the functional condition of the small intestine were used clinical data and results of the load tests by sugars. Cavitary digestion was studied by load test with polysaccharide (soluble starch), membrane digestion - with disaccharide (sucrose), absorption - with monosaccharide (glucose). Glucose level in blood was determined on an empty stomach, then after oral reception of 50g of glucose, sucrose or starch in 30, 60 and 120 minutes.Results. Researchers showed that in the most of patients with cholelithiasis there were disturbances in clinical and functional condition of the small intestine. In an assessment of the cavitary digestion the level of glycemia was authentically lowered by 43% in prestone stage and by 66% in stone stage of cholelithiasis in comparison with control. In an assessment of membrane digestion in patients with the stone stage of cholelithiasis the level of glycemia was lowered in comparison with group of control and with the prestone stage by 30% and 19% respectively.Conclusion. In prestone stage of cholelithiasis there were decrease of the cavitary digestion primary, and in stone stage of cholelithiasis - all stages of hydrolysis-resorptive process in the small intestine were disturbed.